Effect of Corporate Social Responsibility on Company Value With Company Size and Profitability as Moderated Variables in Pharmaceutical Companies Listed on the Indonesia Stock Exchange - Ni Luh Laksmi Rahmantari; Ni Wayan Sitiari; Ida Bagus Agung Dharmanegara (Universitas Warmadewa, 2019)
This study aims to analyze the effect of Corporate Social Responsibility on firm value, the size of the company against firm value, profitability against firm value, company size in moderating the relationship between Corporate Social Responsibility and company value, profitability in moderating the relationship between Corporate Social Responsibility to the value of the company. This study uses a quantitative method which uses time series or past data related to the Annual Report of Pharmaceutical Companies listed on the Indonesia Stock Exchange. The technical data analysis in this study uses Analysis Moderated Regresion with SPSS for Windows 25.0. The sample in this study used eight pharmaceutical companies listed on the Indonesia Stock Exchange. Use annual reports with the 2014-2017 period. The results of the research obtained are Corporate Social Responsibility has a significant positive effect on firm value,Firm size has a significant positive effect on firm value, Profitability has a significant negative effect on firm value, Firm size is not able to moderate relationships between Corporate Social Responsibility (CSR) and company value, Profitability is not able to moderate the relationship between Corporate Social Responsibility (CSR) and company value.